Knowledge, Attitude and Behavior Levels about Osteoporosis among 18-35 Years Old Women - Asım Koç; Cenk Aypak; Hülya Yıkılkan (Galenos Yayinevi, 2016)
Objective: Osteoporosis (OP) which is a global health problem can be prevented or the development of the disease can be delayed. To educate individuals at risk and to intervene in a timely manner will provide significant reduction in morbidity and mortality caused by OP. Possible interventions in the age group of developed OP are important to determine. Therefore, in this study, it was aimed to determine information, attitudes and behaviors levels on osteoporosis at young women. Materials and Methods: This study was carried out among 18-35 years old females who attended to outpatient clinics of Dışkapı Yıldırım Beyazıt Training and Research Hospital Family Medicine Clinic. A questionnaire was used to assess knowledge, beliefs, and practices towards OP. The questionnaire to assess practices related to OP included questions on positive and negative behaviors towards OP. The positive behaviors assessed were dietary calcium intake, physical activity and exposure to sun. The negative behavior assessed was on smoking status. Results: A total of 218 women (mean age= 26.2±5.6 years) were enrolled in the study. The median score of knowledge about OP was 40, out of a total score of 100. Knowledge scores were lower than the median in 138 (63.3%) and were higher than the median in 80 (36.7%) of the participants. In the group who had high knowledge score than median (n=80); 24 (30%) were smokers, 8 (10%) were not exposed to the sun for at least 10 minutes a day and 45 (56.2%) of the participants did not achieve the recommended daily allowances for calcium and 64 (80%) were not engaged in the recommended exercises in type and duration. Conclusion: Awareness for OP is low in young women and practices towards preventing OP are inadequate. Thus, preventive measures are required in order to encourage OP-preventive life style especially before reaching peak bone mass.